Rifaximin: A Unique Gastrointestinal-Selective Antibiotic for Enteric Diseases - Koo, Hoonmo L. (Curr Opin Gastroenterol, 2010)
PURPOSE OF REVIEW: Rifaximin is gaining attention for its potential activity in a multitude of gastrointestinal diseases. We review the unique pharmaceutical properties of this antibiotic and the published evidence in the literature regarding the use of rifaximin for different gastrointestinal disorders. RECENT FINDINGS: Rifaximin is a gastrointestinal-selective antibiotic with a broad spectrum of antimicrobial activity, an excellent safety profile, minimal drug interactions, and negligible impact on the intestinal microbiome. Rifaximin is currently approved in the United States for the treatment of travelers’ diarrhea caused by noninvasive diarrheagenic Escherichia coli and is approved in more than 30 other countries for a variety of gastrointestinal disorders. Considerable research with this medication has been conducted for the treatment and prevention of travelers’ diarrhea, the treatment of portal systemic encephalopathy, Clostridium difficile infection, small bowel intestinal overgrowth, irritable bowel syndrome, inflammatory bowel disease, pouchitis, and colonic diverticular disease. SUMMARY: Rifaximin is effective for the treatment of travelers’ diarrhea and can be considered as the treatment of choice for uncomplicated travelers’ diarrhea. When invasive travelers’ diarrhea pathogens are suspected, an alternative antibiotic should be administered. Rifaximin appears promising as a chemoprophylaxis for travelers’ diarrhea and as a treatment of portal systemic encephalopathy. This antibiotic may be effective for other gastrointestinal diseases, but more well-designed clinical studies are needed to confirm its efficacy for these off-label indications. Future studies will determine whether the development of significant bacterial resistance will limit rifaximin use.